Pengaruh Motivasi, Kepuasan Kerja, Dan Komitmen Kepada Organisasi Terhadap Kinerja Karyawan Pada Divisi Pengendalian Mutu Di Pt Pg Candi Baru, Sidoarjo - Muhammad Ichsan Nugraha; Eko Nurhadi; Pawana Nur Indah (Fakultas Pertanian, Universitas Warmadewa, 2020)
Motivation is the impetus for someone to do something in various activities for which he is responsible. Job satisfaction concerns an individual's general attitude towards his job. Someone with a high level of job satisfaction shows a positive attitude towards their work, while commitment is a level of loyalty to someone like an employee who works optimally for his company. The leaders in the quality control division must pay attention to this, because the motivation given to the quality control division employees is still lacking. In addition, employees with low commitment will also affect their performance. This needs to be considered because the quality control division is an important division and is directly related to the sugar production process. This study aims to determine the effect of motivation, satisfaction and work commitment in the quality control division at PT PG Candi Baru. This research was conducted at PT PG Candi Baru Sidoarjo using primary data. The data collection method used is by conducting interviews and distributing questionnaires to a sample of employees who have worked for at least 5 years. The analysis used in this research is descriptive analysis and correlational analysis. The results showed that motivation and job satisfaction can improve employee performance in the quality control division at PT PG Candi Baru Sidoarjo, while commitment to the organization has not been able to improve employee performance in the quality control division at PT PG Candi Baru Sidoarjo. Motivation, satisfaction and work commitment influence 40% of employee performance, while the remaining 60% are other variables not mentioned in the research.